Manipulating regulatory responses in antitumour immunity - Galvin, Karen (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2011)
The immune system has evolved tolerogenic and regulatory mechanism to control responses to self-antigens and to ensure that the inflammatory immune response to pathogens does not cause excessive tissue damage during infection. Whilst regulatory T cells (Treg) play a pivotal role in maintaining immune tolerance, tumour cells have the capacity to exploit the regulatory mechanisms of the immune system to evade anti-tumour effector immune responses. Immune subversion by tumours, especially their ability to induce or activate Treg cells, is a major barrier in the development of effective immunotherapeutics and vaccines against cancer. Therefore, in order to develop a successful therapeutic vaccine against cancer, immune tolerance must be overcome to allow the generation of anti-tumour CD4+ Th1 cells and CD8+ cytotoxic T lymphocyte (CTL) responses.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin